SPE Latin American and Caribbean Petroleum Engineering Conference 2010
DOI: 10.2118/139020-ms
|View full text |Cite
|
Sign up to set email alerts
|

Casing-Drilling Application in the Depleted La Cira Infantas Mature Field, Colombia

Abstract: Field redevelopment reflects the unique foci of the integrated project team built between Ecopetrol and Oxy to redevelop the LCI oilfield. La Cira Infantas (LCI) is the oldest Colombian field, production started almost at the beginning of the twentieth century and since late 2005 is under a redevelopment phase, increasing production by more than 5 times in less than 5 years. Redevelopment involves over 1500 wells being drilled or worked over in order to increase recovery factor by about 8% from the C sands. Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Although the exact mechanism of the smear effect is not known, pipe size, annular clearance, rotary speed, mud type and penetration rate are the parameters that affect it (Kiran et al, 2014). Researchers reported that DwC technology showed a 10% reduction in cost and 30% savings in time (Lopez and Bonilla, 2010;Sánchez et al, 2012). Other investigators showed that lost circulation was significantly reduced (Fontenot et al, 2003;Karimi et al, 2011) and stated that fracture gradient and wellbore strengthening were improved (Salehi et al, 2013).…”
Section: Drilling With Casing And/or Liner Backgroundmentioning
confidence: 99%
“…Although the exact mechanism of the smear effect is not known, pipe size, annular clearance, rotary speed, mud type and penetration rate are the parameters that affect it (Kiran et al, 2014). Researchers reported that DwC technology showed a 10% reduction in cost and 30% savings in time (Lopez and Bonilla, 2010;Sánchez et al, 2012). Other investigators showed that lost circulation was significantly reduced (Fontenot et al, 2003;Karimi et al, 2011) and stated that fracture gradient and wellbore strengthening were improved (Salehi et al, 2013).…”
Section: Drilling With Casing And/or Liner Backgroundmentioning
confidence: 99%